Midregional proatrial naturetic peptide (MRproANP) and copeptin (COPAVP) as predictors of all-cause mortality in recently diagnosed mild to moderate COPD: results from COSYCONET - Fähndrich, Sebastian Wolfgang; Herr, Christian; Teuteberg, Saskia; Alter, Pascaline; Söhler, Sandra; Soriano, Daniel; Classen, J.; Adams, J.; Weinhold, Valentin; Watz, Henrik; Waschki, Benjamin; Zeller, T.; et al. (Respiratory research, 2024)
MRproANP and COPAVP are prognostic markers for mortality in chronic obstructive pulmonary disease (COPD). Furthermore, these biomarkers predict mortality due to cardiovascular diseases, which are important prognostically determining comorbidities in patients with COPD. However, less is known about these biomarkers in recently diagnosed mild to moderate COPD. Therefore, we analyzed these biomarkers as potential predictors of mortality in recently diagnosed mild to moderate COPD.